DEATH FEAR IN TEACHING PROFESSION IN SECONDARY SCHOOLS IN NSUKKA URBAN - Ugwu, Cosmas Uchenna; Ngwoke, Oliver R. (International Journal of Human Kinetics, Health and Education, 2023)
Death fear is a threat to teaching profession and academic performances particularly in secondary schools. This study determined death fear in teaching profession in secondary schools in Nsukka urban. Three research questions and one null hypothesis of no significant difference guided the study. The study adopted a descriptive research design. A sample size of 260 respondents was randomly selected from thirteen public secondary schools in Nsukka urban of Enugu state. Questionnaire was used as instrument for data collection. Mean, standard deviation and t-test were the statistical tools used for data analysis. The finding indicated that death fear in teaching profession in secondary schools in Nsukka urban is high. Female teachers showed higher death fear in teaching profession than their male counterpart. Year of experience determined death fear in teaching profession. It was recommended among others that Nigerian universities and Colleges of Education should provide more effective death education programmes and courses that can modify the attitudes of students and teachers towards death and death related concepts.